Sistem Informasi Penjualan Kayu dan Keramik Berbasis Website (Studi Kasus: UD. ABC Jendral Sudirman Salatiga) - Putra, Oktavian Alle Mahenswa; Pakereng, Magdalena A.Ineke (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
UD. ABC is a trade unit or shop in the wooden and ceramic fields located in General Sudirman, Argomulyo district of Salatiga City.The system of sales transactions used in this store UD. ABC is still manually by means of recording the sales data on the notebook and after that the data will be written and stored just so, the recording of the sales transaction that is still manual of course is still less effective and at any time the data can be lost.Therefore, there is a need for a website-based information system that can make it easier for employees to record sales transactions. With the presence of a web-based sales application this also makes it easy for employees, because of the large amount of product data and having a large number of customers, with this employee can easily record the sales transaction data and store it and excel form. In this study, it was built using the prototyping method.-based sales information system web designed using the PHP programming language and MySQL database.method black-box testing.